A retrospective population-based study of childhood hospital admissions with record linkage to a birth defects registry - Bower Carol; Colvin Lyn (BMC, 2009)
Abstract Background Using population-based linked records of births, deaths, birth defects and hospital admissions for children born 1980-1999 enables profiles of hospital morbidity to be created for each child. Methods This is an analysis of a state-based registry of birth defects linked to population-based hospital admission data. Transfers and readmissions within one day could be taken into account and treated as one episode of care for the purposes of analyses (N = 485,446 children; 742,845 non-birth admissions). Results Children born in Western Australia from 1980-1999 with a major birth defect comprised 4.6% of live births but 12.0% of non-birth hospital admissions from 1980-2000. On average, the children with a major birth defect remained in hospital longer than the children in the comparison group for the same diagnosis. The mean and median lengths of stay (LOS) for admissions before the age of 5 years have decreased for all children since 1980. However, the mean number of admissions per child admitted has remained constant at around 3.8 admissions for children with a major birth defect and 2.2 admissions for all other children. Conclusion To gain a true picture of the burden of hospital-based morbidity in childhood, admission records need to be linked for each child. We have been able to do this at a population level using birth defect cases ascertained by a birth defects registry. Our results showed a greater mean LOS and mean number of admissions per child admitted than previous studies. The results suggest there may be an opportunity for the children with a major birth defect to be monitored and seen earlier in the primary care setting for common childhood illnesses to avoid hospitalisation or reduce the LOS.